PRODUCT SELLING PRICE DETERMINATION WITH A FULL COSTING APPROACH - Kurniawan, Ridho Raditya (Proceeding International Seminar of Islamic Studies, 2022)
In this study to explain how to determine the selling price carried out by MSMEs Gunung Jaya Binjai based on full costing. In this study using data collection techniques by means of observation, the data source of this study is the 2018 cost report data, the method of analysis used in this study is descriptive quantitative. From the results of the study that MSMEs in Gunung Jaya Binjai in determining the cost of goods used a full costing approach because it takes into account all elements of production costs into the cost of production. MSMEs in Gunung Jaya Binjai have taken into account all cost elements in production costs. MSME Gunung Jaya Binjai also has not included factory overhead costs in determining the price of its production. MSMEs in Gunung Jaya determine the selling price between full costing and variable costs. The high selling price is in a full costing position